2008
DOI: 10.1016/j.ssc.2008.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Bound pairs: Direct evidence for long-range attraction between like-charged colloids

Abstract: We report observations of stable bound pairs in very dilute deionized aqueous suspensions of highly charged polystyrene colloidal particles, with monovalent counterions, using a confocal laser scanning microscope. Through an analysis of several thousands of time series of confocal images recorded deep inside the bulk suspension, we find that the measured pair-potential, U(r) has a long-range attractive component with well depths larger than the thermal energy. These observations provide a direct and unequivoca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 41 publications
8
60
1
Order By: Relevance
“…Before we discuss the origin of split second peak, we would like to mention here that the split peak is genuine and does not arise due to finite thickness of the optical slice. By performing Monte Carlo simulations Tata et al 33 showed that the in-plane g͑r͒ calculated for a slice with thickness close to the optical slice is the same as that of 3D g͑r͒ of a bulk suspension. Hence, the split peak observed in 3D g͑r͒ is genuine and free from projection errors and imaging artifacts.…”
Section: Resultsmentioning
confidence: 98%
“…Before we discuss the origin of split second peak, we would like to mention here that the split peak is genuine and does not arise due to finite thickness of the optical slice. By performing Monte Carlo simulations Tata et al 33 showed that the in-plane g͑r͒ calculated for a slice with thickness close to the optical slice is the same as that of 3D g͑r͒ of a bulk suspension. Hence, the split peak observed in 3D g͑r͒ is genuine and free from projection errors and imaging artifacts.…”
Section: Resultsmentioning
confidence: 98%
“…For example, in the recent experiment on highly deionized water by Tata et al [11], ℓ DB ≈ 500nm, λ Bj ≈ 0.7nm, andT ≈ 1/57; the system is therefore well in the low temperature limit. The problem of dilute electrolytes is therefore simple from the field theory point of view.…”
Section: Appendix B: Some General Results At Saddle Point Levelmentioning
confidence: 93%
“…In that work, the authors take into account all the proposed artefacts to date for their measurements, demonstrating that charged glass surfaces really induce attractions between charged colloidal spheres. Moreover, Tata et al (2008) claim that their observations using confocal laser scanning of millions of charged colloidal particles establish the existence of an attractive behaviour in the electrostatic potential. Moreover, other possible electrostatic variations in these systems may appear for several reasons.…”
Section: Anomalous Effectsmentioning
confidence: 99%